FPGA-based device for handwritten digit recognition in images; Компьютерная оптика; Т. 41, № 6 - Zoev I. V. Ivan Vladimirovich; Beresnev A. P. Aleksey Pavlovich; Markov N. G. Nikolai Grigorevich; Malchukov A. N. Andrey Nikolaevich (2017, 2017)
Заглавие с экрана